2019
DOI: 10.1158/0008-5472.can-18-3704
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic Reordering Induced by Polycomb Loss Drives Oncogenesis but Leads to Therapeutic Vulnerabilities in Malignant Peripheral Nerve Sheath Tumors

Abstract: Malignant peripheral nerve sheath tumor (MPNST) is an aggressive sarcoma with recurrent loss-of-function alterations in polycomb-repressive complex 2 (PRC2), a histone-modifying complex involved in transcriptional silencing. To understand the role of PRC2 loss in pathogenesis and identify therapeutic targets, we conducted parallel global epigenomic and proteomic analysis of archival formalin-fixed, paraffinembedded (FFPE) human MPNST with and without PRC2 loss (MPNST LOSS vs. MPNST RET). Loss of PRC2 resulted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 63 publications
5
45
1
Order By: Relevance
“…An alternative model is direct interference with Polycomb function, which also occurs in many cancers and may lead to hypermethylation [69][70][71]. Our analysis of mESC Polycomb mutants supports a causal association: inactivation of the PRC1.1 variant component Kdm2b leads to significant Fig.…”
Section: Discussionsupporting
confidence: 62%
“…An alternative model is direct interference with Polycomb function, which also occurs in many cancers and may lead to hypermethylation [69][70][71]. Our analysis of mESC Polycomb mutants supports a causal association: inactivation of the PRC1.1 variant component Kdm2b leads to significant Fig.…”
Section: Discussionsupporting
confidence: 62%
“…It is unclear whether these observations are due to alteration of these pathways in the tumor cells or through the reduction of tumor-infiltrating antigen-presenting cells within the tumor. Finally, PRC2 loss was noted to correlate with global DNA hypermethylation at gene promoters and intergenic regions [62]. This DNA hypermethylation was hypothesized by the authors as a potential explanation for the repression of protein expression in the absence of functional PRC2 in MPNSTs.…”
Section: The Biochemical Epigenetic and Transcriptomic Consequencesmentioning
confidence: 85%
“…The identification of IHC screening for H3K27me3 as a reliable biomarker of MPNST led to additional studies that utilized H3K27me3 IHC as a diagnostic marker for MPNST [54][55][56][57][58][59][60][61]. Wojcik and colleagues used this screen to select samples of both PRC2 mutant and PRC2 wildtype status for use in proteomic analyses [62]. These proteomic analyses revealed that the loss of PRC2 caused global changes in post-translational modifications of histones, including 1) a substantial decrease in the transcriptionally repressive modification H3K27me3, 2) broad distribution of the repressive marker H3K27me2, 3) no compensatory gain of other repressive markers, for instance H3K9me3 or H4K20me3, and 4) significant increase in active chromatin markers, including H3K27 acetylation (H3K27ac) and H3K36me2 [62].…”
Section: The Biochemical Epigenetic and Transcriptomic Consequencesmentioning
confidence: 99%
See 2 more Smart Citations